Targeted mapping and utilization of the perihepatic surface for therapeutic beta cell replacement and retrieval in diabetic non-human primates - Leishman, David J.; Oppler, Scott H.; Stone, Laura L. Hocum; O’Brien, Timothy D.; Ramachandran, Sabarinathan; Willenberg, Bradley J.; Adams, Andrew B.; Hering, Bernhard J.; Graham, Melanie L. (Frontiers in Transplantation, 2024)
Successful diabetes reversal using pancreatic islet transplantation by various groups illustrates the significant achievements made in cell-based diabetes therapy. While clinically, intraportal islet delivery is almost exclusively used it is not without obstacles including instant blood-mediated inflammatory reaction (IBMIR), relative hypoxia, and loss of function over time therefore hindering long-term success. Here we demonstrate the perihepatic surface of nonhuman primates (NHPs) as a potential islet delivery site maximizing favorable characteristics including proximity to a dense vascular network for adequate oxygenation while avoiding IBMIR exposure, maintenance of portal insulin delivery and relative ease of accessibility through minimally invasive surgery or percutaneous means. Additionally, we demonstrate a targeted mapping technique of the perihepatic surface allowing for testing of multiple experimental conditions including a semi-synthetic hydrogel as a possible three-dimensional framework to improve islet viability. Perihepatic allo-islet cell transplants were performed in immunosuppressed cynomolgus macaques using a targeted mapping technique to test multiple conditions for biocompatibility. Transplant conditions included islets or carriers (including hydrogel, autologous plasma, and media) alone or in various combinations. Necropsy was performed at d30 and histopathology was performed to assess biocompatibility, immune response, and islet viability. Subsequently, single-injection perihepatic allo-islet transplant was performed in immunosuppressed diabetic cynomolgus macaques. Metabolic assessments were measured frequently (i.e. blood glucose, insulin, C-peptide) until final graft retrieval for histopathology. Targeted mapping biocompatibility studies demonstrated mild inflammatory changes with islet-plasma constructs however significant inflammatory cell infiltration and fibrosis was seen surrounding sites with hydrogel carrier affecting islet viability. In diabetic NHPs, perihepatic islet transplant using an autologous plasma carrier demonstrated prolonged function up to 6 months with improvements in blood glucose, exogenous insulin requirements and HbA1c. Histopathology of these islets were associated with mild peri-islet mononuclear cell infiltration without evidence of rejection. The perihepatic surface serves as a viable site for islet cell transplantation demonstrating sustained islet function through 6 months. The targeted mapping approach allows for testing of multiple conditions simultaneously to evaluate immune response to biomaterials at this site. Compared to traditional intraportal injection, the perihepatic site is a minimally invasive approach that allows the possibility for graft recovery and avoids IBMIR.